Chronic hepatitis C: Diagnosis and treatment made easy - Naim Abu-Freha (European Journal of General Practice, 2022)
Background Hepatitis C Virus (HCV) is a common cause of chronic liver disease and its ensuing complications. In the last years, there has been a revolution of the treatment for patients with HCV regarding efficacy, simplicity, safety and duration of treatment. The role of the family physician is vital in all steps of care: screening, diagnosis, linkage to treatment, treatment and follow-up.Objectives This review aims to summarise the family physician and the important updated recommendations for diagnosis and treatment of patients with chronic HCV.Methods The updated recommendations were reviewed and summarised in a short and simple review.Results Patients with any risk factor for HCV should first be screened for HCV antibodies. In the case of positive antibodies, reflex testing for RNA polymerase chain reaction (PCR) should be done without waiting for genotype. For patients with positive PCR, fibrosis assessment should be conducted using laboratory panels (Fibrosis-4 index (FIB-4) or aspartate aminotransferase to platelet ratio index (APRI)); if advanced fibrosis is suspected, additional non-invasive fibrosis assessment is needed, such as fibrotest or liver elastography. Naïve non-cirrhotic or compensated cirrhosis (Child-Pugh-Score A) could be treated with pangenotypic drugs, Glecaprevir/pibrentasvir (Maviret) for eight weeks, or Sofosbuvir/velpatasvir (Epclusa) for 12 weeks.Conclusion Patients without advanced fibrosis and comorbidities can be treated by the educated family physician. However, patients with comorbidities, cirrhosis or coinfection (HIV, Hepatitis B Virus (HBV)) should be referred to the liver clinic. In case of screening patients with risk factors or likelihood of dormant HCV, health organisations should provide the appropriate resources, logistics, finances and workforce.